Unravelling the interaction between the DRD2 and DRD4 genes, personality traits and concussion risk. Issue 1 (2nd February 2019) - Abrahams, Shameemah; McFie, Sarah; Lacerda, Miguel; Patricios, Jon; Suter, Jason; September, Alison V; Posthumus, Michael
Abstract : Background: Concussion occurs when biomechanical forces transmitted to the head result in neurological deficits. Personality may affect the balance between safe and dangerous play potentially influencing concussion risk. Dopamine receptor D2 ( DRD2 ) and dopamine receptor D4 ( DRD4 ) genetic polymorphisms were previously associated with personality traits. Objectives: This case–control genetic association study investigated the associations of (1) DRD2 and DRD4 genotypes with concussion susceptibility and personality, (2) personality with concussion susceptibility and (3) the statistical model of genotype, personality and concussion susceptibility. Methods: In total, 138 non-concussed controls and 163 previously concussed cases were recruited from high school (n=135, junior), club and professional rugby teams (n=166, senior). Participants were genotyped for DRD2 rs12364283 (A>G), DRD2 rs1076560 (C>A) and DRD4 rs1800955 (T>C) genetic variants. Statistical analyses including structural equation modelling were performed using the R environment and STATA. Results: The rs1800955 CC genotype (p=0.014) and inferred DRD2 (rs12364283–rs1076560) –DRD4 (rs1800955) A–C–C allele combination (p=0.019) were associated with decreased concussion susceptibility in juniors. The rs1800955 TT and CT genotypes were associated with low reward dependence in juniors (p<0.001) and seniors (p=0.010), respectively. High harm avoidance was associated with decreased concussion susceptibility in juniors (p=0.009) and increased susceptibility in seniors (p=0.001). The model showed that a genetic variant was associated with personality while personality was associated with concussion susceptibility. Conclusion: These findings highlight the linear relationship between genetics, personality and concussion susceptibility. Identifying a genetic profile of 'high risk' behaviour, together with the development of personalised behavioural training, can potentially reduce concussion risk.